The Effect of the Effectiveness of Accounting Information Systems and the Use of Accounting Information Technology on Individual Performance at Perumda BPR Majalengka - Purnama Sari, Indah; Wida R, Melia; Riyadi, Wulan; Rahman, Erpi (Finance and Business Management Journal, 2023)
Perumda BPR Majalengka is also inseparable from the existing problems. Regarding the alleged corruption of Perumda BPR Majalengka Branch Sukahaji valued at Rp. 3.2 billion which was suspected of committing irregularities in 2017-2021. This study aims to determine the effect of the effectiveness of accounting information systems and the use of accounting information technology on individual performance at Perumda BPR Majalengka. This research is qualitative research using primary data obtained from questionnaires and measured using a Likert scale. This sampling technique uses a saturated sampling technique. By using a sample of 54 employees of Perumda BPR Majalengka. Data analysis used descriptive analysis, classical assumption test, multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing with the help of SPSS version 26. The results of the research show that the effectiveness of accounting information systems and the use of accounting information technology has a positive and significant effect on individual performance, either partially or simultaneously.